1981
DOI: 10.1007/bf02774385
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of appearance of serum γ-glutamyl transpeptidase isozyme

Abstract: Serum gamma-glutamyl transpeptidase zymograms were examined by 4--26% polyacrylamide gradient gel slab electrophoresis using sera from 90 patients with various hepatobiliary diseases. The isozyme bands were separated into 13 bands in order from post albumin fraction. Characteristic patterns of the zymograms were obtained in cases of hepatocellular carcinoma and cholestasis. Bands I, II and II' may be specifically related to hepatocellular carcinoma. Band I was observed frequently in hepatocellular carcinoma, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It is thus necessary to search for new markers of hepatoma in addition to AFP determination. Some investigators, using polyacrylamide gel gradient electrophoresis, have fractionated 1-3 bands of GGT specific for hepatoma with a positivity rate of only 27-63% (Sawabu et al, 1977(Sawabu et al, , 1983Kojima et al, 1980;Suzuki, 1981). In our laboratory, adopting the method of vertical slab stage electrophoresis on polyacrylamide gel, we have been able to fractionate a total of 9-11 activity bands of GGT, in which GGT I T is found in sera from almost all patients with hepatoma.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is thus necessary to search for new markers of hepatoma in addition to AFP determination. Some investigators, using polyacrylamide gel gradient electrophoresis, have fractionated 1-3 bands of GGT specific for hepatoma with a positivity rate of only 27-63% (Sawabu et al, 1977(Sawabu et al, , 1983Kojima et al, 1980;Suzuki, 1981). In our laboratory, adopting the method of vertical slab stage electrophoresis on polyacrylamide gel, we have been able to fractionate a total of 9-11 activity bands of GGT, in which GGT I T is found in sera from almost all patients with hepatoma.…”
Section: Discussionmentioning
confidence: 84%
“…, 1977(Sawabu et a/. , , 1983Kojima et al, 1980;Suzuki, 1981) with evidence of diagnostic value in hepatobiliary pathology, particularly hepatoma. We have been able to separate a GGT-11 band with stage electrophoresis on polyacrylamide gel (Xu et al, 1983), but the percentage of positive results in hepatoma was too low (29.1 %) to permit clinical application.…”
mentioning
confidence: 99%
“…Since then, other methods have been used, that is, separation of GGT bands by means of starch gel (Orlowski and Szczeklik, 1967), cellulose acetate (Hitoi et al, 1984), agarose gel (Hetland et al, 1975), polyacrylamide gel electrophoresis (Kojima et al, 1980;Suzuki et al, 1981;Sawabu et al, 1983;Kew et al, 1984), and polyacrylamide stage gel plate (Xu et al, 1985). The polyacrylamide stage gel plate method allows detecting positivity up to 90% in hepatoma patients (Xu et al, 1985).…”
mentioning
confidence: 99%
“…22 In recent years, Asian researchers documented the presence of up to 11 serum GGT isoenzymes, and showed that the faster isoforms (bands I-II) are often present in the serum of HCC patients. [23][24][25][26][27] In the 1980s, an Italian group developed an electrophoretic procedure for the analysis of GGT isoenzymes. Of the five different isoenzymatic bands that could be distinguished, the one that comigrates with serum albumin (alb-GGT) appeared to be promising for the diagnosis of both primary and secondary liver tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The complexes occur in the serum as a consequence of the GGT overexpression from neoplastic liver cells and of the biliary impairment typical of the neoplastic liver, and they produce the GGTL isoform that has been found to have a sensitivity of 80% and a diagnostic accuracy of 92% at a cut‐off value of 20 U/L 22 . In recent years, Asian researchers documented the presence of up to 11 serum GGT isoenzymes, and showed that the faster isoforms (bands I–II) are often present in the serum of HCC patients 23–27 . In the 1980s, an Italian group developed an electrophoretic procedure for the analysis of GGT isoenzymes.…”
Section: Introductionmentioning
confidence: 99%